THE ROLE OF STATE REVENUE IN ACHIEVING SUSTAINABLE DEVELOPMENT GOALS - Nikmatul Ulfa Maghfiroh; Cahyatik (Assets Journal: Journal of Economic and Business, 2025)
Sustainable development as stated in the Sustainable Development Goals (SDGs) requires significant financial resources to achieve a balance between economic, social, and environmental needs. Sources of state revenue, including taxes, Non-Tax State Revenue (PNBP), and grants, play an important role in supporting the achievement of the SDGs. Taxes contribute more than 80% of state revenue, while PNBP and grants also provide support for strategic development programs. However, the management of these revenue sources faces various challenges, such as low tax compliance, dependence on natural resources (SDA), and inefficiency in grant management. This study uses a descriptive qualitative approach with secondary data analysis from government reports, regulations, scientific journals, and statistical documents. The results show that taxes are the main source of funding for the education, health, and infrastructure sectors, while PNBP supports economic diversification through the management of natural resources, state-owned enterprises, and public services. Grants support strategic projects, such as climate change mitigation and disaster management. However, the main challenges of dependence on SDA and grants, as well as the need for tax reform, need to be addressed. The proposed optimization strategies include reforming the tax system, diversifying revenue sources, increasing financial transparency, and strengthening international cooperation to achieve sustainable development goals.